2008
DOI: 10.1007/s10712-008-9042-2
|View full text |Cite
|
Sign up to set email alerts
|

Ice and Snow Cover of Continental Water Bodies from Simultaneous Radar Altimetry and Radiometry Observations

Abstract: We show how the studies of ice and snow cover of continental water bodies can benefit from the synergy of more than 15 years-long simultaneous active (radar altimeter) and passive (radiometer) observations from radar altimetric satellites (TOPEX/Poseidon, Jason-1, ENVISAT and Geosat Follow-On) and how this approach can be complemented by SSM/I passive microwave data to improve spatial and temporal coverage. Five largest Eurasian continental water bodies-Caspian and Aral seas, Baikal, Ladoga and Onega lakes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 52 publications
3
19
0
2
Order By: Relevance
“…Extreme temperature conditions contribute to the changing Caspian Sea level while the annual component has an amplitude of approximately 20 mm as reported in Swenson and Wahr (2007). A detailed discussion on the ice cover of the Caspian Sea as well as the techniques for detecting them from remote sensing observations are documented, e.g., in Kouraev et al (2003Kouraev et al ( , 2004Kouraev et al ( and 2008.…”
Section: The Caspian Seamentioning
confidence: 93%
See 1 more Smart Citation
“…Extreme temperature conditions contribute to the changing Caspian Sea level while the annual component has an amplitude of approximately 20 mm as reported in Swenson and Wahr (2007). A detailed discussion on the ice cover of the Caspian Sea as well as the techniques for detecting them from remote sensing observations are documented, e.g., in Kouraev et al (2003Kouraev et al ( , 2004Kouraev et al ( and 2008.…”
Section: The Caspian Seamentioning
confidence: 93%
“…Ignatov et al (1993), for example, explained the cause of these fluctuations to be possibly climatic, and that it is dependent on the water budget of its basin (precipitation and river recharge minus water loss by evaporation). Impact of ice coverage changes on the level variations of the Caspian and its detecting using altimetry data sets is discussed, e.g., in Kouraev et al (2003Kouraev et al ( , 2004Kouraev et al ( and 2008. Short-term wind-induced fluctuations are known to cause a rise of up to 4 m, although the average fluctuation is about one meter.…”
Section: Introductionmentioning
confidence: 99%
“…En effet, le signal altimétrique en bande Ku pénètre la neige à l'inverse du signal en bande Ka (37 GHz) bloqué à la surface, ce qui par différence permet d'obtenir des cartes de neige sur tout l'Arctique. Une méthode similaire a été développée au lac Baïkal pour estimer l'épaisseur de la couverture neigeuse sur la glace à partir des observations micro-ondes passives des altimètres et du radiomètre spatial SSM/I (Kouraev et al, 2008).…”
Section: Hauteur De Neige éQuivalent En Eau Et Teneur En Eau Liquideunclassified
“…No attempts were made to isolate or distinguish data points over the lake surface covered by ice or snow from those over water surface in this analysis. However, it should be noted that Kouraev et al (2008) reported a reliable method of ice discrimination in Lake Baikal based on a joint classification of altimeter backscatter coefficient and a radiometer parameter.…”
Section: Envisat Data Analysismentioning
confidence: 99%
“…Also, because of calm waters of rivers and lakes, the waveforms often are specular echoes (Gommenginger et al 2011) having a peak amplitude that is significantly increased rendering the retrackers unsuitable based on the Brown ocean model (Brown 1977). Strong peaky echoes are returned also from thin sea-ice (Peacock and Laxon 2004;Kouraev et al 2008).…”
Section: Introductionmentioning
confidence: 99%